Luminescence characteristics and kinetic parameters of LiBaPO4: Tb3+, Dy3+ phosphors synthesized by sol-gel method - Katı, Mehmet İsmail; Gokce, Sibel; Keski?n, İlker Çetin; Türemiş, Murat; Çetin, Ahmet; Kibar, Rana (Elsevier B.V., 2024)
LiBaPO4: Tb3+, Dy3+ phosphors were prepared via sol-gel method by using the stoichiometric amounts of lithium nitrate LiNO3, barium nitrate Ba(NO3)2 and ammonium dihydrogen phosphate NH4H2PO4 as base materials. Morphology by scanning electron microscopy (SEM), structure by X-ray diffraction (XRD), thermal properties by Differential thermal analysis (DTA)/Thermogravimetric Analysis (TGA) and structural characteristics by Fourier transform infrared spectroscopy (FT-IR) were investigated. This paper presents luminescence properties using spectra from radioluminescence (RL), photoluminescence (PL), cathodoluminescence (CL) and, thermoluminescence (TL) and the influence of RE dopants (Tb3+, Dy3+) on the luminescent behavior of LiBaPO4. Computerized Glow Curve Deconvolution (CGCD) and Peak Shape Method were used to determine the kinetic parameters and the obtained results were evaluated. The RL results of un-doped LiBaPO4 showed the presence of a well-defined peak at 417 nm and a weaker band around 685 nm. Strong emissions were detected in the sample doped with Dy3+ correspond to 4F9/2?6Hj transitions. Blue, yellow and red emissions were observed with transitions of 4F9/2 ? 6H15/2, 4F9/2 ? 6H13/2 and 4F9/2 ? 6H11/2, respectively. As for LiBaPO4: Tb3+, green emissions originated from the characteristic transitions (5D3 ? 7FJ (j = 6–3) and 5D4 ? 7FJ (j = 6–1)) of Tb+3 ion was seen. The RL, PL and CL spectra were identical, suggesting these green emissions. Dy3+ doped sample has three glow curves located at 72 °C, 145 °C and 204 °C, while the main temperature peak is measured at 240 °C for Tb3+ doped sample. Chromotographic studies of LiBa0·98PO4: Dy3+0.02 reveals that calculated x and y color coordinates (0.3122, 0.3233) are very close to the white light. © 2023
Keywords: Cathodoluminescence; Kinetic parameters; LiBaPO4; Photoluminescence; Radioluminescence; Rare earth; Sol-gel; Thermoluminescence